The effectiveness of blooket on students’ vocabulary learning among secondary school students - Sinaga, Nurleli; Widyantoro, Agus; Sinaga , Aulia Nurjannah (Indonesian Research Journal in Education |IRJE|, 2025)
This research investigated the effectiveness of Blookets, a gamified learning platform, in improving EFL students’ vocabulary learning. This research employed a quasi-experimental design with a mixed-methods approach. The research collected quantitative data through vocabulary pre- and post-tests comprising 40 multiple-choice items, which were analyzed using SPSS version 30. Qualitative data were obtained through semi-structured interviews and were thus analyzed thematically. The results indicated that students in the experimental group demonstrated significantly higher vocabulary scores than those in the control group, mainly due to Blooket’s multimodal features such as real-time feedback and spaced repetition. Additionally, students expressed positive perceptions of the platform, highlighting enhanced enjoyment, practicality, reinforcement, motivation, and positive recommendations. These findings suggest that integrating a gamified learning platform like Blookets into vocabulary instruction offers a practical and engaging strategy for promoting language learning outcomes in secondary education.